Academic Achievement in Analytic Geometry and Calculus for Teachers about Limits and Continuity using Teaching that Emphasizes Conceptualization with the GeoGebra Program for Undergraduate Students - Khatbanjong, Suriyun (Journal of Education Studies, Chulalongkorn University, 2025)
The objectives of this research were to study the results of organize learning activities on the topic of Limit and Continuity in Analytic Geometry and Calculus for Teachers Course based on using a Concept Enhancement Teaching Method and GeoGebra Program. The sample consisted of 18 bachelor’s degree students at a university in Bangkok. A purposive sampling method was used. The research instrument were a 10-items learning achievement test with a reliability of 0.84 and a satisfaction survey. Regarding the statistical measure, t-test was employed. Findings indicate that: 1) the efficiency of the learning activity plan is 77.83/76.90, which meets the criterion, 2) the learning achievement after the usage is significantly higher than before the usage at .05, and 3) the overall satisfaction is at the highest level with an average of (M = 4.66, SD = 0.08).